2005
DOI: 10.1021/om050171i
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Synthesis of Oligoynes Capped by a Ru2(ap)4-terminus and Their Electrochemical and Optoelectronic Properties

Abstract: Cross-coupling reactions between terminal ethynes (HC⋮CY) and Ru2(ap)4(C2( k - 1)H) under Hay conditions, where ap is 2-anilinopyridinate and k = 2−5, resulted in compounds Ru2(ap)4(C2kY) (Y = Si i Pr3 and Ph) along with the homocoupling products YC4Y and [Ru2(ap)4]2(μ-C4( k - 1)). Compounds Ru2(ap)4(C2 k Y) display two reversible Ru2-based one-electron couples:  an oxidation and a reduction. The HOMO−LUMO gaps (E g) estimated from electrode potentials correlate linearly with the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 89 publications
3
48
0
Order By: Relevance
“…[20] Interestingly, an increment of + 30 to + 50 mV in the value of E ox was observed with each additional triple bond for compounds 1-4. As noted previously for 1 and 2, [23] and for some oligoyne-bridged binuclear organometallic compounds, [32,33] this can be ascribed to the electron-withdrawing nature of the extra triple bond. In the present D-(C C) n -A systems we cannot exclude the possibility that charge delocalisation across the bridge might play a role in causing these anodic shifts.…”
Section: Introductionsupporting
confidence: 72%
“…[20] Interestingly, an increment of + 30 to + 50 mV in the value of E ox was observed with each additional triple bond for compounds 1-4. As noted previously for 1 and 2, [23] and for some oligoyne-bridged binuclear organometallic compounds, [32,33] this can be ascribed to the electron-withdrawing nature of the extra triple bond. In the present D-(C C) n -A systems we cannot exclude the possibility that charge delocalisation across the bridge might play a role in causing these anodic shifts.…”
Section: Introductionsupporting
confidence: 72%
“…38 Also very recently, Goodson, Ren et al reported the synthesis of a structurally related series of ruthenium-capped oligoynes. 39 These oligomers were prepared by a crosscoupling reaction between terminal acetylenes [HC≡CY, Y = Si(i-Pr 3 ), Ph] and Ru 2 (ap) 2 (C 2(k-1) H) (ap = 2-anilinopyridinate, k = 2-5).…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Tykwinski and co-workers reported regioselective Diels-Alder reaction of different hexatriynes (14)(15)(16)(17)(18)(19)(20) with tetraphenylcyclopentadienone followed by further CO extrusion (Scheme 2). [60] As a result variety of hexasubstituted benzenes (21)(22)(23)(24)(25)(26)(27)(28) were obtained.…”
Section: Polyynes As Well As Acetylenes May Undergo Different [2+2] Omentioning
confidence: 99%
“…[63,64] Depending on polyyne end-groups and structure of the carbene, different types of products were observed. The use of bulkier TIPS group (14) led to product where the middle triple bond was involved in the reaction (45). The use of bulkier TIPS group (14) led to product where the middle triple bond was involved in the reaction (45).…”
Section: Polyynes As Well As Acetylenes May Undergo Different [2+2] Omentioning
confidence: 99%
See 1 more Smart Citation